1987
DOI: 10.1007/bf00290085
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA amplification in cultured cells of Oryza sativa L.

Abstract: Highly repeated nuclear DNA sequences from suspension cultured cells of Oryza sativa L. cv. 'Roncarolo' have been cloned in pBR322. Ten clones with specific digestion patterns have been randomly selected. Nine sequences appear to be organized in a clustered tandem array while one is interpersed in the rice genome. The clones have been used to gather information on: (a) their modulation in cultured cells as compared to whole plant and (b) their distribution in different rice cultivars belonging to the Japonica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…However, changes affecting only a proportion of regenerants would probably have gone undetected in this experiment, and the process of regeneration may select against genomic variants produced in tissue culture. Other studies have demonstrated changes in the copy number of repeated DNA families in rice tissue culture (18,19).…”
Section: Resultsmentioning
confidence: 94%
“…However, changes affecting only a proportion of regenerants would probably have gone undetected in this experiment, and the process of regeneration may select against genomic variants produced in tissue culture. Other studies have demonstrated changes in the copy number of repeated DNA families in rice tissue culture (18,19).…”
Section: Resultsmentioning
confidence: 94%
“…However, other known mechanisms might play a role in our study as well, such as (a) a differential transposition of somatically active transposable elements, which have been described in, so far, both invertebrates and vertebrates [43,44] or (b) the presence of heritable changes involving DNA within a single generation that have been observed in the annual flax [45]. We cannot exclude from our consideration the possibility of environmentally induced changes of genome size, as these changes have been observed during cell culturing [46][47][48]. Also, observed genome size changes may have been associated (not necessarily directly selected for) with changes in cell volume and/or in karyoplasmatic ratio.…”
Section: Selection For Genome Size In Cyclamen?mentioning
confidence: 96%
“…Such rearrangements can be of two types, first, loss of hybridization fragments characteristic for one of the parental species, or second, the occurrence of new fragments which are not present in the parental genomes. Several investigations have shown that amplification and deletion of chromosomal regions or specific DNA sequences is a common reaction of plant genomes to various stress factors (ZHENG et al 1987;LAPI-TAN et al 1988;MOORE and SINK 1988;KIDWELL and OSBORN 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific DNA probes were first used for the identification of somatic hybrids by SAUL and POTRYCUS (1984). Such studies mostly describe amplification and deletion of repetitive DNA sequences (ZHENG et al 1987;LAPITAN et al 1988). These effects are usually explained by the stress influence of in vitro cultivation.…”
mentioning
confidence: 99%